Day-of-the-week effect among the smallest enterprises listed on WSE - Jakub Keller (e-Finanse: Financial Internet Quarterly, 2015)
The text touches on the subject of the financial markets in the context of behavioral theories. The author attempts to verify the occurrence of one of the popular calendar effects, the day-of-the-week effect, on the Polish stock market. Another limitati on of the study area of the research is to include in the analysis only small companies. Many voices from the mainstream of behavioral finance say that the presence of anomalies listed is more evident in the case of small companies, which are not the focus of the majority of investors. In the proposed study, the data used contained companies in the Stock Exchange in Warsaw, with a maximum capitalization of 10 million PLN. Research sample includes quotations of these companies during the period January 2010-April 2014. In order to verify the hypothesis of the occurrence of the day-of-the-week effect among these companies the author used ARCH modeling. In the course of the analysis the author verifi ed negatively the occurrence of the effect of weekdays in the proposed research sample.
Keywords: G14; 330; stock markets; stock anomalies; calendar anomalies; Warsaw Stock Exchange